EKSPLORASI KAPANG PENDEGRADASI MINYAK SOLAR PADA RIZOSFER MANGROVE, CILACAP - Syah, Ryan F.; Irianto, A.; Ratnaningtyas, N. I. (BIOEDUKASI, 2013)
The aims of this research was to explore and collect diversity of hydrocarbon degrader mold isolated from Mangrove Forest Tritih Kulon, Cilacap, Central Java. Identification of mold was conducted base on the characteristis of colony, cell shape, color of colony. Result of this research, it was obtained 4 hydrocarbon degrader mold. They were 2 genera; Penicillium and Aspergillus. Quality degradation test showed that Aspergillus sp. could degradated 40% diesel oil.Â Key word: mold, mangrove, hydrocarbon degrader.